2002
DOI: 10.1016/s0168-9452(02)00320-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of genes preferentially expressed in cotton fibers by cDNA filter arrays and RT-PCR

Abstract: Cotton fibers are single-cell trichomes derived from the outer integument cells of ovules. Recent studies showed that the rapid elongation of fibers was coordinated with the expression of a subset of fiber-specific genes. Here we report the use of filter arrays of cDNAs to identify genes preferentially expressed in cotton fibers. An array of 1536 clones was hybridized with cDNA probes prepared from wild type (fiber-containing) and fl mutant (naked) ovules at 5 days post-anthesis (DPA), respectively. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 38 publications
1
67
0
3
Order By: Relevance
“…Our previous study showed that transcripts of a cotton RDL gene were enriched in developing fiber cells (Li et al, 2002). DNA gel blot hybridization revealed two RDL genes, namely RDL1 and RDL2, in the genome of G. arboreum (see Supplemental Figure 1 online), an A-genome diploid cotton cultivar (Rong et al, 2004).…”
Section: Expression Pattern Of Cotton Rdl1mentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study showed that transcripts of a cotton RDL gene were enriched in developing fiber cells (Li et al, 2002). DNA gel blot hybridization revealed two RDL genes, namely RDL1 and RDL2, in the genome of G. arboreum (see Supplemental Figure 1 online), an A-genome diploid cotton cultivar (Rong et al, 2004).…”
Section: Expression Pattern Of Cotton Rdl1mentioning
confidence: 98%
“…Analyses of gene expression patterns have identified numerous genes whose transcripts are enriched in fiber cells (John and Crow, 1992;Li et al, 2002;Ji et al, 2003), including those encoding metabolism enzymes that are essential to cell growth (Pear et al, 1996;Ruan et al, 2003). For transcription factors, a noteworthy work is the isolation of six MYB genes from G. hirsutum (Loguerico et al, 1999;Cedroni et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of fibers npg isolated from the 3 DPA ovules was also checked under a microscope. Total RNA was isolated from the -3 to 5 DPA ovules and the 6 to 24 DPA fibers by a cold-phenol method as described previously [27,28]. Poly (A)+RNA was purified by an Oligotex mRNA Midi kit (Qiagen, Valencia, CA, USA) according to the manufacturer's instruction, and cDNA libraries were constructed following the ZAPcDNA Synthesis kit (Stratagene, La Jolla, CA, USA).…”
Section: Rna Extraction and Library Constructionmentioning
confidence: 99%
“…Further investigation by KOBAS [27] mapped 1 116 out of the 5 122 cotton ESTs to 164 pathways, and 152 stage-differential genes to 85 pathways. After hyper geometric distribution and FDR corrections, seven metabolic pathways involving secondary metabolite, fatty acid and carbohydrate metabolisms show significant changes (q < 0.05) during cotton fiber development (Table 2).…”
Section: Changes Of Metabolites In Developing Fibersmentioning
confidence: 99%
“…These early studies were followed by genomics approaches, including Expressed Sequence Tag (EST) library sequencing and microarray hybridization. In particular, EST libraries corresponding to various stages of development were produced and these provide invaluable resources for the identification of fiber specific genes (Li et al, 2002a;Arpat et al, 2004;Udall et al, 2006;Yang et al, 2006). As genes from these EST collections start being characterized, more information has become available on the pattern of expression and the importance of some transcription factors in fiber development (Lee et al, 2007).…”
Section: Genomics Of Cotton Fibersmentioning
confidence: 99%